2017
DOI: 10.1007/s12272-016-0868-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel oleanolic acid and ursolic acid in C-28 position derivatives as potential anticancer agents

Abstract: A series of nitrogen-containing derivatives of oleanolic acid and ursolic acid were prepared by a modification at C-28 position via esterification with 2-hydroxyacetic acid followed by amidation with amines, such as piperazine, N-methylpiperazine, and alkane-1, 2-diamines, alkane-1, 4-diamines, alkane-1, 6-diamines. In vitro antiproliferative activities of the compounds prepared towards MCF-7, Hela and A549 cell lines were evaluated by a MTT method to show that OA-5a, OA-5b, OA-5c and UA-5a showed somewhat imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…They further dissolved the intermediate in dichloromethane to give a series of amino compounds including aminobenzene, p-fluoroaniline, p-chloroaniline, p-bromobenzenamine, p-methoxylaniline o-fluoroaniline, o-chloroaniline and o-bromobenzenamine through condensation in the presence of triethylamine. After this, saponification analogues (62-69) were produced, which were later hydrolysed to give more derivatives (70)(71)(72)(73)(74)(75)(76)(77). Lastly, the 3-oxo anlogue (78) was developed through oxidation with pyridinium chlorochromate.…”
Section: Chemistry Of Uamentioning
confidence: 99%
See 2 more Smart Citations
“…They further dissolved the intermediate in dichloromethane to give a series of amino compounds including aminobenzene, p-fluoroaniline, p-chloroaniline, p-bromobenzenamine, p-methoxylaniline o-fluoroaniline, o-chloroaniline and o-bromobenzenamine through condensation in the presence of triethylamine. After this, saponification analogues (62-69) were produced, which were later hydrolysed to give more derivatives (70)(71)(72)(73)(74)(75)(76)(77). Lastly, the 3-oxo anlogue (78) was developed through oxidation with pyridinium chlorochromate.…”
Section: Chemistry Of Uamentioning
confidence: 99%
“…Many researchers, in search of more bioactive compounds, have reported different UA derivatives. Herewith are some of UA analogues with interesting mechanisms related to currently existing non-communicable diseases utilizing positions C-2, C-3, C-20 and C-28 ( Figure 11) [69][70][71][72][73]. One UA derivative compound, 118 (2α,3β,7β,23-tetrahydroxyurs-12-ene-28-oic acid) ( Figure 11), is a naturally occurring compound isolated from Castanea crenata Sieb.…”
Section: Chemistry Of Uamentioning
confidence: 99%
See 1 more Smart Citation
“…One of these semi-synthetic products, 3β-acetoxyursolic acid [1-(2-aminoethylamino)-1-oxo] ethyl ester (14) (▶ Fig. 3), was found to exhibit discernible cytotoxicity, showing an IC 50 value in the range 8-10 µM, while, the IC 50 values of (+)-ursolic acid (11) were greater than 100 µM for all these 3 cancer cell lines used [58].…”
Section: Ursane-type Triterpenoidsmentioning
confidence: 99%
“…Ursolic acid (UA) is a pentacyclic triterpene, which is widely distributed throughout the whole plant kingdom, and is a major component of some traditional medicinal plants [13]. It has been found to have anti-cancer and anti-hyperlipidemia effects [14][15][16]. In our previous study, we reported the synergistic effects of artesunate and ursolic acid on lipid reduction and anti-atherosclerosis [17].…”
Section: Introductionmentioning
confidence: 99%